One-Stop Dispensing: Hospital Costs and Patient Perspectives on Self-Management of Medication - Morten Baltzer Houlind; Helle Bach Ølgaard McNulty; Charlotte Treldal; Signe Lindgaard Andersen; Thomas Huneck Haupt; Janne Petersen; Ove Andersen; Lene Juel Kjeldsen (MDPI AG, 2018)
(1) Objective: To assess hospital medication costs and staff time between One-Stop Dispensing (OSD) and the Traditional Medication System (TMS), and to evaluate patient perspectives on OSD. (2) Methods: The study was conducted at Hvidovre Hospital, University of Copenhagen, Denmark in an elective gastric surgery and acute orthopedic surgery department. This study consists of three sub-studies including adult patients able to self-manage medication. In Sub-study 1, staff time used to dispense and administer medication in TMS was assessed. Medication cost and OSD staff time were collected in Sub-study 2, while patient perspectives were assessed in Sub-study 3. Medication costs with two days of discharge medication were compared between measured OSD cost and simulated TMS cost for the same patients. Measured staff time in OSD was compared to simulated staff time in TMS for the same patients. Patient satisfaction related to OSD was evaluated by a questionnaire based on a five-point Likert scale (‘very poor’ (1) to ‘very good’ (5)). (3) Results: In total, 78 elective and 70 acute OSD patients were included. Overall, there was no significant difference between OSD and TMS in medication cost per patient ($2.03 [95% CI −0.57–4.63]) (p = 0.131). Compared with TMS, OSD significantly reduced staff time by an average of 12 min (p ≤ 0.001) per patient per hospitalization. The patients’ satisfaction for OSD was high with an average score of 4.5 ± 0.7. (4) Conclusion: There were no differences in medication costs, but staff time was significantly lower in OSD and patients were overall satisfied with OSD.